VisualEars: How an immersive art exhibit impacts mood during the COVID-19 pandemic - Hadavi, Shafagh; Kennedy, Kody G.; Mariotti, Geneva; DeSouza, Joseph F. X. (Frontiers in Psychology, 2022)
This paper explores the positive impact of viewing a virtual art exhibit on mood during the COVID-19 Pandemic. During global lockdowns, depression, anxiety, and the burden of other mental illnesses have increased even among prior psychiatrically healthy individuals. Art and music-based interventions have shown to be effective clinical interventions in individuals with mental illness. The VisualEars project explored whether a virtual activity involving vision and auditory stimuli could improve positive and negative affect. Eight musical pieces were selected, and 28 visual artists from around the world visualized two musical pieces. A total of 56 works of art were created and hung in eight 3D virtual rooms. Visitors were randomly selected to either view the art exhibit without music (non-immersive) or view the art exhibit while listening to music (immersive). Visitors were asked to complete a positive and negative affect schedule (PANAS) in three languages (English, French, and Farsi) pre and post their virtual visit. A total of 160 participants completed baseline PANAS, 58 of which completed the follow-up PANAS. Linear mixed-effects models found that older participants had lower negative affect scores overall (b = −0.3, p = 0.003), while male participants had lower positive affect scores overall (b = −0.27, p = 0.02). Following the virtual exhibit participants of both conditions had higher positive (b = 0.17, p = 0.03), and lower negative affect scores (b = −0.19, p = 0.007). We found that the virtual art exhibit increased positive affect and decreased negative affect in participants, suggesting an overall improvement in mood attributable to the virtual exhibit. This suggests that virtual exhibits may serve as a beneficial and accessible intervention to improve mood during a pandemic.